An Integrated Value-Based Framework for Modeling Strategic Decision Analysis and Planning in Public Agricultural Corporations in Sudan: The case of the Gezira Scheme. - Abdalla, Abdalla Khidir (Gezira Journal of Economic and Social Sciences; Vol 9 No 1 (2018), 2018)
Towards addressing the complexity of the problems facing Public Agricultural Corporations (PACs) in Sudan, this paper highlights the need to adopt a value-based approach to strategic planning. Directing attention to strategic decision analysis and planning system (SDAPS) in PACs will assist in halting, repairing, and preventing the current deterioration. The framework detailed in this paper enables efficient and effective utilization of the capital input and available resources toward meeting stakeholders’ expectations and the PACs’ objectives, nicely illustrating a quintessential “win-win” scenario. Additionally, this framework can serve as a comprehensive and straight forward path for the implementation of strategic decision making and planning in similar large organizations in other sectors.